Financial liquidity as a factor determining the economic condition of companies on the capital market in relation to bankruptcy law in Poland - Monika Bolek; Agata Gniadkowska-Szymańska (e-Finanse: Financial Internet Quarterly, 2019)
The aim of this article is to present financial liquidity as a factor affecting the economic condition of the companies on the capital market in relation to the amended Bankruptcy Law in Poland. A study was carried out to determine the impact of liquidity on the increase in earnings per share and return on assets, indicators can be used to assess the economic condition of a company. As a result, logit and quadratic functions were examined and the parameters of the models provided a verification of the hypothesis. As a result, it was found that the good economic situation of a company related to the increase in earnings per share and profitability is affected by the increasing cash efficiency of assets and the decreasing value of the current ratio. It can therefore be concluded that according to theory, conducting a more aggressive policy in the area of liquidity results in an increase in the value of an economic entity and, therefore, its good economic condition, but the effect of overly aggressive policies may influence solvency, which is defined by Bankruptcy Law.
Keywords: G1; G28; G33; 330; financial liquidity; bankruptcy; the economic condition of companies